Tough guys - Gradert, Kenyon (Dissent, 2017)
In The End of Eddy—an autobiographical novel written by Édouard Louis, formerly Eddy Bellegueule—looks upon butchers and bullies with striking empathy, less as brutes than as actors forced by working-class life into preordained roles. As "the faggot," Eddy is beaten to the bottom of dramatis personae because that's what "tough guys" do in this tragedy. To survive, Eddy tries to don the tough-guy costume but fails entirely. Like the crippled scapegoats of ancient Greece, he's beaten and ultimately exiled in a bid for purification during social crisis. Everyone sees through Eddy's act but misses their own.
Gesehen am 18.08.2021